An Application of Generative Learning Models to Improve Students Learning Outcomes of Geography at X-IPS 3 Class Sma Negeri 1 Pekanbaru In academic year 2019/2020 - Gusti, Jendri Afriwal; Lawita, Nadia Fathurrahmi (Sumatra Journal of Disaster, Geography and Geography Education, 2020)
This research is motivated by the low learning outcomes of student at geography subject. The aims of this research was to obtain the information and discuss the efforts to improve student learning outcomes of Geography subject through the application of generative learning models at X-IPS3 class in SMA Negeri 1 Pekanbaru in academic year 2019/2020. This research was a classroom action research that consisting of two cycles, where is each cycle consisted of four stages namely planning, acting, observing, and reflecting. The subject of this research was at X-IPS 3 class in SMA Negeri 1 Pekanbaru. The research was conducted in Odd Semester 2019 in the 2019/2020 of academic years. Data collection techniques by interviewing and observing students in class while studying for 2 months starting from September to October 2019. The results showed that through generative learning models could improve student-learning outcomes of geography at X-IPS 3 class in SMA Negeri 1 Pekanbaru 2019/2020 academic year.